2015
DOI: 10.7717/peerj.1208
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Critical Care Family Need Inventory to the Turkish population and its psychometric properties

Abstract: In the complex environment of intensive care units, needs of patients’ relatives might be seen as the lowest priority. On the other hand, because of their patients’ critical and often uncertain conditions, stress levels of relatives are quite high. This study aims to adapt the Critical Care Family Need Inventory, which assesses the needs of patients’ relatives, for use with the Turkish-speaking population and to assess psychometric properties of the resulting inventory. The study was conducted in a state hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
2
16
0
2
Order By: Relevance
“…Unmet of the parental needs increases the stress and can lead to situation crisis. Many studies have highlighted the importance of identification the needs of family members in order to enable the health care providers in providing adequate emotional and physical support to family members [2,12,13]. A qualitative study to identify the perceived needs of Saudi families of patients in Intensive Care indicated that almost all family participants do not aware about the prognosis of their ill relative and this leads to deep feeling of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Unmet of the parental needs increases the stress and can lead to situation crisis. Many studies have highlighted the importance of identification the needs of family members in order to enable the health care providers in providing adequate emotional and physical support to family members [2,12,13]. A qualitative study to identify the perceived needs of Saudi families of patients in Intensive Care indicated that almost all family participants do not aware about the prognosis of their ill relative and this leads to deep feeling of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies revealed that patient's physical condition, unfamiliar ICU environment, restriction of visitors, use of sophisticated equipment, different sounds and alarms are the major sources of stress for ICU patients and their relatives. 2,3 The critically ill patients are not usually able to make their treatment decisions and family members or relatives are responsible for it. 4 However, their ability to provide support to the patient and cooperation with health personnel is disturbed because of emotional distress so they need greater physical and psychological support from the health personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Sudden serious illness of any member creates a crisis not only for the individual patient but also for the family members 1 . Each family member plays a supportive role for its members in crisis which is reflected in care and support during illness 2 . Family members go through painful experiences when a relative is admitted to an intensive care unit (ICU) 3 .…”
Section: Introductionmentioning
confidence: 99%